Correlated electrons in a zig-zag chain with the spin-orbit interaction: Exact solution - Zvyagin, A.A. (Физика низких температур, 2018)
The correlated electron model on a geometrically frustrated one-dimensional lattice with the spin-orbit coupling is studied. The exact solution is obtained using the Bethe ansatz. Zig-zag interaction can produce incommensurate charge and spin structures for large enough frustrating interactions. The spin-orbit coupling yields the
behavior of correlation functions, reminiscent of the Fulde–Ferrell–Larkin–Ovchinnikov (FFLO) features of real
type-II superconductors. Вивчаєтся модель корельованих електронів на геометрично
фрустрованій одновимірній гратці зі спін-орбітальною взаємодією. Одержано точне вирішення методом анзаца Бете. Взаємодія на гратці типу зигзаг може призвести до появи несорозмірних структур для великих значень фруструючих взаємодій.
Спін-орбітальна взаємодія призводить до поведінки кореляційних функцій, які нагадують особливості типу Фульде–Ферреля–Ларкіна–Овчинникова в реальних надпровідниках другого роду Изучается модель коррелированных электронов на геометрически фрустрированной одномерной решетке со спинорбитальным взаимодействием. Получено точное решение
методом анзаца Бете. Взаимодействие на решетке типа зигзаг
может привести к появлению несоизмеримых структур для
больших значений фрустрирующих взаимодействий. Спинорбитальное взаимодействие приводит к поведению корреляционных функций, напоминающих особенности типа Фульде–
Ферреля–Ларкина–Овчинникова в реальных сверхпроводниках второго рода.